2020
DOI: 10.1360/tb-2020-0190
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the cure rate and case fatality rate of the ongoing epidemic COVID-19

Abstract: The epidemic caused by the novel coronavirus COVID-19 in Wuhan at the end of 2019 has become an urgent public event of worldwide concern. However, due to the changing data of the epidemic, there is no scientific estimate of the cure rate and case fatality rate of the epidemic. This study proposes a method to estimate the cure rate and case fatality rate of COVID-19. The ratio of cumulative discharges on a given day to the sum of cumulative discharges on a given day and cumulative deaths before j days is used t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For Beijing, (1) disease surveillance, crowd control in supermarkets, and food and customs surveillance efforts need to be strengthened. (2) The sanitation emergency plan needs to be improved and followed up on, and the staffs of various units need to be closely and continuously monitored, especially those who are in close contact with seafood or refrigerated food, to prevent the occurrence of infections. (3) Since natural environmental variables have played a certain role in the model evaluations conducted herein, we should guide residents to consider proper indoor ventilation in autumn and winter and raise residents' awareness of the "early detection, early reporting, early isolation, and early treatment" of illness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Beijing, (1) disease surveillance, crowd control in supermarkets, and food and customs surveillance efforts need to be strengthened. (2) The sanitation emergency plan needs to be improved and followed up on, and the staffs of various units need to be closely and continuously monitored, especially those who are in close contact with seafood or refrigerated food, to prevent the occurrence of infections. (3) Since natural environmental variables have played a certain role in the model evaluations conducted herein, we should guide residents to consider proper indoor ventilation in autumn and winter and raise residents' awareness of the "early detection, early reporting, early isolation, and early treatment" of illness.…”
Section: Discussionmentioning
confidence: 99%
“…The new coronavirus disease is highly infectious and has a long incubation period with the potential for no symptoms. To date, abundant literature has indicated that the crude mortality ratio (the number of reported deaths divided by the number of reported cases) is between 2-3%, which is slightly higher than that of common influenza and lower than that of SARS [1,2]. As of 23 April 2020, 2,544,792 COVID-19 cases, including 175,694 attributable deaths, have been reported worldwide [3].…”
Section: Introductionmentioning
confidence: 99%